Metal Complexes of π-expanded Ligand (5): Synthesis, Structural, and Photophysical Characterizations of Green-Red Luminescent Pyrene-based Salicylaldiminato-type Zinc Complexes - Xuan Dien, Luong; Nga, Nguyen Thi Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 2DO - 10.25073/2588-1140/vnunst.5153, 2021)
A series of pyrene-based salicylaldimine-type ligands containing n-octyl or cyclohexyl or phenyl groups at imine nitrogen group, 1-hydroxy-2-[(N-substituted-imino)methyl]-pyrenes (octyl 1, cyclohexyl 1b and phenyl 1c), were synthesized and characterized. The ligands reacting with zinc acetate in the presence of sodium acetate gave the bis(salicylaldiminato)-type Zn(II) complexes, [bis[2-[(N-substituted-imino)methyl]-1-pyrenolato-N,O] zinc(II)] (octyl 1(Zn), cyclohexyl 1b(Zn), phenyl 1c(Zn)). The new ligands and complexes were characterized by 1 H NMR, IR spectroscopy, mass spectroscopy, elemental analysis, UV-vis spectroscopy, fluorescence spectroscopy, and X-ray diffraction. The influence of the π-extended conjugation of the pyrene-based salicylaldiminato-type ligands coordinated to Zn 2+ greatly induces red-shift of the complexes 1(Zn), 1b(Zn) and 1c(Zn) in absorption and emission spectra. These results were confirmed by density-functional theory (DFT) and time-dependent DFT (TDDFT) molecular orbital calculations. Moreover, single crystal structure of simple salicylaldiminato Zn(II) complex 1’b(Zn) was compared to that of the corresponding pyrene-type salicylaldiminato complex 1b(Zn).